2003
DOI: 10.1002/poc.698
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of substituted 2‐furaldehydes by quinolinium dichromate: a kinetic study

Abstract: The kinetics of oxidation of substituted 2‐furaldehydes by quinolinium dichromate in sulfuric acid, using 50% acetic acid as the solvent, was studied. The rate of the reaction was first order in each of the substrate, oxidant and acid. The kinetic data are discussed with reference to the aldehyde hydration equilibria. The kinetic results support a mechanistic pathway proceeding via a rate‐determining oxidative decomposition of the chromate ester of the aldehyde hydrate. Copyright © 2003 John Wiley & Sons, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…Kinetics of oxidation of benzaldehyde by various oxidizing agents have been well studied [3][4][5][6][7][8][9][10] . A search of literature revealed that only few reports are available for kinetics of oxidation of heterocyclic aldehydes [11][12][13][14][15][16] .…”
Section: Research Articlementioning
confidence: 99%
See 1 more Smart Citation
“…Kinetics of oxidation of benzaldehyde by various oxidizing agents have been well studied [3][4][5][6][7][8][9][10] . A search of literature revealed that only few reports are available for kinetics of oxidation of heterocyclic aldehydes [11][12][13][14][15][16] .…”
Section: Research Articlementioning
confidence: 99%
“…FT-IR spectra were obtained as KBr discs on Shimadzu spectrometer. 1 H NMR (500 MHz) and 13 C NMR (125 MHz) spectra was obtained using Bruker DRX-500 Avance at ambient temperature, using TMS as internal standard. Mass spectra were determined on a Varion -Saturn 2000 GC/MS instrument.…”
Section: Product Analysismentioning
confidence: 99%
“…Quinolinium chlorochromate 14 is a stable reagent originally introduced as an oxidizing agent for alcohol is used in synthetic organic chemistry [15][16][17][18][19][20] . The kinetic mechanistic aspects of oxidation reactions by QCC reports are available in the literature [21][22][23][24][25][26] The kinetics of oxidation of Phenols by various oxidizing reagents have been well studied 27-29 . Phenol is so inexpensive that it attracts many small-scale uses. It once was widely used as an antiseptic, especially as carbolic soap.…”
Section: Introductionmentioning
confidence: 99%
“…The use of quinolinium chloro chromate has an oxidant is well documented for the oxidation of primary and secondary alcoholorganic sulphides substituted benzaldehydes, benzyl alcohols [10] , Aromatic anils , lactic and glycolic acid, methionine [11] , D-fructose [12] , D -Mannos, unsaturated organic substrate [13] , acrylic acid, 2-Furaldehyde [14] and D-galactose etc.…”
mentioning
confidence: 99%